Alcohol, masculinity, honour and male barroom aggression in an Australian sample - Miller, P.; Wells, S.; Hobbs, R.; Zinkiewicz, L.; Curtis, A.; Graham, Kathryn (Wiley-Blackwell Publishing Ltd., 2014)
Introduction and Aims: The link between alcohol and men’s aggression is well established, although growing evidence also points to individual and learned social factors. The aim of the present study was to investigate the relationships between male alcohol-related aggression (MARA) among young Australian men and heavy episodic drinking, trait aggression, masculinity, concerns about social honour and expected positive consequences of MARA. Design and Methods: The total sample comprised 170 men aged 18–25 years who completed an online questionnaire exploring beliefs and attitudes towards MARA. Results: Those who reported heavy episodic drinking were more likely to be involved in an incident of MARA. In addition, those who were involved in MARA had higher levels of trait aggression, concern for social honour and expected positive consequences of aggression in bars than did those without such involvement. The relationship between socially constructed masculinity factors (a combined variable reflecting masculinity, social honour and expected positive consequences) and MARA was mediated by heavy episodic drinking. Social honour accounted for almost all of the predictive power of masculinity factors. Heavy episodic drinking and trait aggression remained significant predictors of MARA in a multivariate model. Discussion and Conclusions: The findings from the current study may assist in developing preventative techniques for young men which target masculinity concerns and the consequences of participating in MARA. [Miller P, Wells S. Alcohol, masculinity, honour and male barroom aggression in an Australian sample.